Elevated expression of ANTXR1 gene in tumors is a poor prognostic biomarker for patients with bladder cancer - Franco, L. S.; Arunachalam, S.; Chauhan, A.; Kareff, S. A.; Hallenbeck, P. L. (Frontiers in Molecular Biosciences, 2025)
The TEM8 protein coded by the ANTXR1 gene represents an emerging biomarker in solid tumors. In addition to the various roles TEM8 plays in oncogenesis, including angiogenesis, epithelial-to-mesenchymal transition, and cell migration, it has also been shown that the overexpression of the ANTXR1 gene in solid tumors correlates with poor prognostic indicators in several solid tumor histologies. As such, TEM8 has been identified as the target of novel oncologic therapies. It is especially attractive given its selective expression on the surface of solid tumor cells and associated stromal cells, such as cancer stem cells, invasive cancer cells, and immune cells, such as macrophages, angiogenic endothelial cells, pericytes, and cancer-associated fibroblasts. Furthermore, TEM8 plays this unique role as a mostly non-mutated gene in solid cancers. Here, we demonstrate that elevated expression of ANTXR1 in bladder cancer showed a statistical difference not only in overall survival (OS) but in progression-free survival (PFS), confirming the prognostic biomarker power of ANTXR1 expression.